The acquisition of L2 fricatives in Thai learners’ interlanguage - Sridhanyarat, Kietnawin (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research examined how Thai undergraduates acquired English marked and unmarked fricatives in their interlanguage. It also determined what sounds the learners used to replace some fricatives and how variable they were. Based on the Markedness Differential Hypothesis (MDH), unmarked fricatives are /s/ and /f/, and marked ones are /ʃ/, /v/, /z/, /θ/, /ð/, and /ʒ/. The former are considered unmarked because they are available in Thai, whereas the latter are not. The participants included three groups: high, intermediate, and low proficiency students who were studied through three types of tasks: word list, sentence list, and oral interview. The word and sentence lists required the learners to produce the target fricatives in a formal situation, while the oral interview in a natural context. The results demonstrated that marked fricatives /v/, /z/, /θ/, /ð/, and /ʒ/ were difficult for the participants. Only the advanced informants could acquire unmarked /s/ and /f/ as well as marked /ʃ/ both initially and finally. According to the MDH, the learners produced /s/, /f/, and /ʃ/ before marked /v/, /z/, /θ/, /ð/, and /ʒ/. They also appeared to produce various substitutions for the problematic sounds. Plausible explanations to account for the Thai learners’ difficulty of English fricatives involve the first language (L1) transfer, distribution of a particular sound, voicing, systematic variability, and design of a task. In pronunciation classes, teachers or educators may design tasks appropriate for their learners and employ strategies that suit their learning style preferences.